Combatting African Animal Trypanosomiasis (AAT) in livestock: The potential role of trypanotolerance - Yaro, M.; Munyard, K.; Stear, M.; Groth, David (Elsevier Science, 2016)
African Animal Trypanosomiasis (AAT) is endemic in at least 37 of the 54 countries in Africa. It is estimated to cause direct and indirect losses to the livestock production industry in excess of US$ 4.5 billion per annum. A century of intervention has yielded limited success, owing largely to the extraordinary complexity of the host-parasite interaction. Trypanotolerance, which refers to the inherent ability of some African livestock breeds, notably Djallonke sheep, N'Dama cattle and West African Dwarf goats, to withstand a trypanosomiasis challenge and still remain productive without any form of therapy, is an economically sustainable option for combatting this disease. Yet trypanotolerance has not been adequately exploited in the fight against AAT. In this review, we describe new insights into the genetic basis of trypanotolerance and discuss the potential of exploring this phenomenon as an integral part of the solution for AAT, particularly, in the context of African animal production systems.